OPTIMIZING POTATO PRODUCTIVITY IN FOOD GRAIN-BASED ORGANIC FARMING SYSTEM UNDER SPRINKLER IRRIGATION - Rawal, Sanay; Mankar, Pooja; Luthra, Satish Kumar; Lal, Mehi; Kumar, Manoj; Dua, Vijay Kumar; Pandey, Narendra Kumar (Potato Journal, 2022)
Field trials were carried during 2013-16 in randomized block design for groundnut-potato-maize+greengram system consisting seven organic input treatment combinations. For crop raising, regional recommendations were adopted, and their nutritional requirement in various organic treatments was calculated as per their recommended inorganic doses. Cultural weed control was followed, and disease-pest management was done through permitted organic means. Observations of growth, yield attributes and yield were recorded for all component crops of the system. Process grade tuber yield improved from 10.5 t/ha to 18.5 t/ha, while total tuber yield increased from 59.9% to 88.3% from first to third year. Tuber weight loss (18.8%) reduced drastically in organic system (IA) over inorganic nutrition (24.5%) at 90 days under ambient storage conditions. System productivity of organic system (IA) improved to 91.3% of inorganic nutrition in third year. Organic system (IA) observed lower net returns in first year, while improvement was observed in third year as this gap reduced to 16.7%. This study suggests that sustainable potato yields can be harnessed in food grain-based cropping systems by including leguminous crops and integrating different organic nutrient sources.